Influence of number and orientation of screws on stability in the internal fixation of unstable femoral neck fractures - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2014)
Objective: The aim of this study was to biomechanically compare 3 different cannulated screw configurations used in internal fixation of unstable femoral neck fractures. Methods: The study included 28 synthetic left femurs randomly divided into 4 equal groups. Samples in the first 3 groups were osteotomized in the basicervical region to create Pauwels Type 3 fractures. Fixation was carried out using cannulated screws. In Group 1, four screws were used including 3 in an inverted triangle configuration in parallel with the neck and the fourth screw transversely into the calcar. In Group 2, three screws were used including 2 in parallel with the neck and the third transversely into the calcar. In Group 3, three screws were used in an inverted triangle configuration in parallel with the neck. No osteotomy or fixation was carried out in Group 4. Load test was performed on all the groups and the strength of the screw fixations against axial load and their amount of relocation were measured. Results: Average maximum strength was 36.1 +/- 3.2 N/mm(2) in Group 1, 27.3 +/- 4.1 N/mm(2) in Group 2 and 21.9 +/- 3.2 N/mm(2) in Group 3. The average relocation in the line of osteotomy in the moment of average maximum stress (21.9 +/- 3.2 N/mm(2)) was 11.5 +/- 2.1 mm in Group 3,6 +/- 1.3 mm in Group 2 and 5.8 +/- 1.1 mm in Group 1 (p<0.05). It was also observed that while the relocation in the moment of average maximum stress (27.3 +/- 4.1 N/mm(2)) was 9.1 +/- 1.7 mm in Group 2, the deformation under the same stress value was 9 +/- 1.7 mm in Group 1 (p>0.05). Conclusion: The use of a transverse screw in the calcar in addition to cannulated screws parallel to the neck appear to provide stability benefit in the treatment of unstable femoral neck fractures.
Keywords: Cannulated screw; femoral neck fractures; fixation; unstable; INTRACAPSULAR FRACTURES; PAUWELS CLASSIFICATION; SLIDING SCREW; MANAGEMENT; IMPLANT